Accompanying People Affected by Cancer in Their Return to Life After Treatment: A Report on an Experiment Conducted in Canada - Christine Arsenault; Saskia Hazout; John Calogerinis; Françoise Poirier; Louise Normandin; Cécile Vialaron; Monica Iliescu Nelea; Marie-Pascale Pomey (Patient Experience Journal)
This study aims to assess family doctors' perceived needs for improved patient follow-up post-acute treatment in oncology departments, specifically focusing on the Patient Oriented Discharge Summary (PODS) for individuals living with cancer. A cross-sectional quantitative survey targeted family doctors, and a before/after exploratory study was conducted with patients to measure their needs pre- and post-PODS implementation. Twenty-one out of 42 family doctors participated in the survey (50%). Patient data was collected at three points in time: prior to PODS implementation (T1, n = 20/30; 77%), one month later (T2, n = 20/26; 77%), and six months later (T3, n = 21/28; 75%). Descriptive statistics were used for all inquiries. Results revealed that 52.24% of family doctors lacked information from oncology teams about patient treatments and their progress, while 90.48% received no guidance on monitoring patients for symptoms or necessary tests once treatment was completed, despite everyone expressing the desire to perform such monitoring. Family doctors recommended using standardized sheets with patient information (47%), details of side effects (41%), and post-treatment follow-up plans (12%). At T1, 60% of patients received the necessary information, at T2 95% and 81% at T3. Regarding instructions provided to family caregivers, satisfaction levels were 40% at T1, 90% at T2, and 62% at T3. The study underscores the imperative of enhancing communication between oncology specialists and family physicians, facilitating the latter's follow-up of patients completing acute treatment. It also highlights the need for patients to be adequately prepared for the transition through effective use and sustained use of PODS.